Women’s Participation in Local Governments of Nepal: Assessing Local Elections of 2017 and 2022 - Timilsina, Krishna Prasad (Prithvi Academic Journal, 2024)
The Federal Republic of Nepal was established after the second people's movement in 2006. The movement was for more political rights after the 1990 political change in the country. As a result, through the incorporation of inclusive principles into Nepal's constitution, women's representation has been mandated across all sectors of the state, including at the local level. This paper aims to examine the legal provisions and practices concerning gender-balanced seat allocation in key municipal positions, such as chief and deputy chief, chairperson and vice-chairperson, in which at least one occupant must be female. It seeks to understand the reasons behind the political parties nominating women candidates for these positions and whether they are considered reservations for women. Using primary field visits and secondary sources, descriptive analytical and content analysis methods were used to make conclusions about the representation of deputy chief and deputy chairperson in the local elections of 2017 and 2022. The study shows that inclusion is emphasised in Nepal's constitution and other legislation, which require women to be represented in all fields. In the 2017 and 2022 local elections, women held 92% and 74% of the deputy positions, respectively. However, neither politically nor constitutionally, the office of deputy chief is solely reserved for women. The analysis sheds light on the motivations behind political parties nominating women candidates for these positions and explores whether they are perceived as reservations for women.